ANALISIS PARAMETER ANGIN MATAHARI TERKAIT BADAI GEOMAGNETIK MENGGUNAKAN METODE DETRENDED FLUCTUATION ANALYSIS (DFA) - Husna, Miftahul
Sweetened conditions of the Sun and a complex process continuously produces a stream of particles known as the Solar wind. High-speed propagation of the Sun's wind by carrying plasma and magnetic fields until it reaches the Earth produces geomagnetic storms that have the potential to cause impacts on the Earth's environment, such as increasing ozone concentrations and even causing temperatures to rise on the Earth's surface in the long term. The Detrended Fluctuation Analysis (DFA) method is applied to review the nature and general patterns of fluctuations in solar wind parameters as a function of time on samples of strong class geomagnetic storm events. The results of the correlation study obtained the parameters of the westward aurora electrojet index (AL index) dominated for positive correlation to the Dst index parameters, while the dominance of negative correlations was given by the Kp*10 index parameters. The results of data extraction of solar wind physical parameters using the DFA method presented Hurst exponents with an overall ? range obtained of 0<????<5.67. The minimum and maximum phases of the selected Solar cycle show the predominance of persistent processes with an overall ???? range obtained of 0.53<????<0.96. The results of data extraction on samples of strong class geomagnetic storm events six days before the peak of strong class geomagnetic storms, dominated by persistent processes with an overall range of ? obtained 0.02<????<5.62. For samples of events on the day of the peak of a strong class geomagnetic storm, nonstationary processes predominate with an overall range of 0<????<5.6. As for the event sample six days after the peak of the strong class geomagnetic storm, the persistent process predominates with an overall ? range obtained of 0<????<3.23.